Singaporeans’ perception of multi-level marketing and an introductory guide to MLM. - Koh, Liwen. (2009)
Multi-level Marketing (MLM) is considered a fairly new business model in Singapore as compared to other countries like the USA. There has been much interest in the MLM industry since its deregulation on 1st June 2000, and there is much more hype surrounding the industry in recent years. The crux of this study is to investigate Singaporeans’ general perspective towards the industry and to research for the possible explanation that leads to the perspective. In addition to that, information on some MLM companies in Singapore will be presented, and a short study of Sunshine Empire (Pyramid Scheme) will be presented as a contrast.